Listening in: Identifying Considerations for Integrating Complementary Therapy into Oncology Care Across Patient, Clinic, and System Levels—A Case Example of a Digital Meditation Tool. - Godinho, Alexandra; Dalmia, Sanvitti; Joshi, Krutika; Seo, Christina; Laj, Suzi; Cacao, Francis; Lun, Lisa; Wegier, Pete; Rana, Punam (Current Oncology, 2025)
Simple Summary: As cancer survival rates and treatment improve, there is a growing interest in adding supportive complementary therapies, like meditation, to standard patient care to help individuals cope with their illness. This study explored how digital meditation tools and complementary therapies in general can be introduced into clinics by examining patient needs and barriers, as well as the realities of clinical settings. Cancer patients currently receiving chemotherapy completed self-report questionnaires to assess their stress level, as well as attitudes, interest, and knowledge of meditation. Results from the 148 participants surveyed showed that while most had never meditated, almost half were interested in trying a digital meditation tool. Interest was highest among women, younger patients, and those already engaging in stress-reducing activities such as prayer or listening to music. Combining these findings with clinical staff discussions, we provide a structured way of examining patient, clinic, and hospital-level factors that may impact the integration of supportive therapies into clinical care. Such an approach can ensure that supportive therapies are tailored to patient needs, are successful, and sustainable for clinics. Purpose: As cancer treatments and survival rates continue to improve, integrating supportive complementary therapies into oncology practice is increasingly important. Identifying patient- and clinic-level considerations can guide the selection and integration of evidence-based and effective therapies. Using the Behavioural Design Space (BDS), this study illustrates how a design framework can facilitate the identification of patient needs, clinic requirements, and system-level constraints prior to implementing a digital meditation tool (DMT). Methods: A cross-sectional survey of cancer patients in active treatment to assess distress, attitudes, barriers, and knowledge of meditation. Descriptive statistics and binary multivariate logistic regressions examined associations between patient characteristics and interest in meditation or using a DMT. Findings were mapped onto the six elements of the BDS framework in consultation with clinic staff. Results: Among 148 patients surveyed, 65% had never meditated, yet 42% expressed interest in using a DMT. Greater engagement in stress-coping activities was the strongest predictor of interest in both learning meditation and using a DMT. Female sex increased, while age decreased, the odds of interest in using a DMT. Conclusions: Integrating complementary therapies into oncology care requires attention to patient, clinic, and system-level factors. The BDS framework can guide the therapy/tool selection process by highlighting patient needs, potential barriers, and implementation challenges. Future work should focus on operationalizing the BDS into a practical decision-making tool for healthcare providers.